Application of amphiregulin in IVM culture of immature human oocytes and pre-insemination culture for COCs in IVF cycles - Fan, Yongqi; Wang, Jing; Ye, Tingting; Yang, Dandan; Zhang, Qiqi; Zhang, Chao; Yan, Bo; Wang, Qiushuang; Ding, Ding; Chen, Beili; Zou, Weiwei; Ji, Dongmei; et al. (Frontiers in Endocrinology, 2024)
Background: Amphiregulin (AR) is a growth factor that resembles the epidermal growth factor (EGF) and serves various functions in different cells. However, no systematic studies or reports on the role of AR in human oocytes have currently been performed or reported. This study aimed to explore the role of AR in human immature oocytes during in vitro maturation (IVM) and in vitro fertilization (IVF) in achieving better embryonic development and to provide a basis for the development of a pre-insemination culture medium specific for cumulus oocyte complexes (COCs).Methods: First, we examined the concentration of AR in the follicular fluid (FF) of patients who underwent routine IVF and explored the correlation between AR levels and oocyte maturation and subsequent embryonic development. Second, AR was added to the IVM medium to culture immature oocytes and investigate whether AR could improve the effects of IVM. Finally, we pioneered the use of a fertilization medium supplemented with AR for the pre-insemination culture of COCs to explore whether the involvement of AR can promote the maturation and fertilization of IVF oocytes, as well as subsequent embryonic development.Results: A total of 609 FF samples were examined, and a positive correlation between AR levels and blastocyst formation was observed. In our IVM study, the development potential and IVM rate of immature oocytes, as well as the fertilization rate of IVM oocytes in the AR-added groups, were ameliorated significantly compared to the control group (All P < 0.05). Only the IVM-50 group had a significantly higher blastocyst formation rate than the control group (P < 0.05). In the final IVF study, the maturation, fertilization, high-quality embryo, blastocyst formation, and high-quality blastocyst rates of the AR-added group were significantly higher than those of the control group (All P < 0.05).Conclusion: AR levels in the FF positively correlated with blastocyst formation, and AR involvement in pre-insemination cultures of COCs can effectively improve laboratory outcomes in IVF. Furthermore, AR can directly promote the in vitro maturation and developmental potential of human immature oocytes at an optimal concentration of 50 ng/mL.